2017
DOI: 10.1126/science.aai8792
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of fat cells from myofibroblasts during wound healing

Abstract: Although regeneration through the reprogramming of one cell lineage to another occurs in fish and amphibians, it has not been observed in mammals. We discovered in the mouse that during wound healing, adipocytes regenerate from myofibroblasts, a cell type thought to be differentiated and nonadipogenic. Myofibroblast reprogramming required neogenic hair follicles, which triggered bone morphogenetic protein (BMP) signaling and then activation of adipocyte transcription factors expressed during development. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
462
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 465 publications
(479 citation statements)
references
References 108 publications
15
462
1
1
Order By: Relevance
“…During wound healing, defects in adipogenesis can abrogate fibroblast recruitment into wound beds, leading to defects in extracellular matrix deposition and tissue repair (3). Migration of adipocyte precursors into the wounded area might also contribute to the mesenchymal repopulation of the wounded site (4) and in wounds where hair follicle neogenesis is observed fully functional adipocyte precursors are present (5). These findings highlight the breadth of the role of adipose tissue in the skin.…”
mentioning
confidence: 82%
“…During wound healing, defects in adipogenesis can abrogate fibroblast recruitment into wound beds, leading to defects in extracellular matrix deposition and tissue repair (3). Migration of adipocyte precursors into the wounded area might also contribute to the mesenchymal repopulation of the wounded site (4) and in wounds where hair follicle neogenesis is observed fully functional adipocyte precursors are present (5). These findings highlight the breadth of the role of adipose tissue in the skin.…”
mentioning
confidence: 82%
“…Interestingly, a recent study has demonstrated that myofibroblasts have the capacity to transdifferentiate to adipocytes in response to bone morphogenetic protein (BMP) signals arising from hair follicles in the healing wound (85), suggesting that preadipocytes are not the only cell type that can give rise to mature fat cells in the dermis.…”
Section: Extrinsic Factors Governing Fibroblast Cellular Identitymentioning
confidence: 99%
“…There is a small number of hair follicles with very sparse density in the normal hand and foot, compared with the rest of the body. We recently reported that fat regeneration can be committed through hair follicles and finely regulated by myofibroblasts [13]. Simultaneously, in human, subcutaneous fat regeneration is highly synchronized with the cyclic patterns of hair follicles [27].…”
Section: Discussionmentioning
confidence: 99%
“…We employed and modified the methods previously reported by our group [13][14][15]. First, we sorted the expression data in excel sheet.…”
Section: Statistical Analysis and Visualizationmentioning
confidence: 99%
See 1 more Smart Citation